Types of Ethical Problems and Expertise in Clinical Ethics Consultation in Psychiatry – Insights From a Qualitative Empirical Ethics Study - Haltaufderheide, Joschka; Gather, Jakov; Juckel, Georg; Schildmann, Jan; Vollmann, Jochen (Frontiers in Psychiatry, 2021)
Background: Ethics consultation has been advocated as a valuable tool in ethically challenging clinical situations in healthcare. It is paramount for the development and implementation of clinical ethics support services (CESS) in psychiatry that interventions can address the moral needs of mental health professionals adequately and communicate the nature of the services clearly. This study explores types of ethical problems and concepts of ethical expertise as core elements of CESS in mental healthcare with the aim of contributing to the further development of ethical support in psychiatry. Methods: We conducted 13 semi-structured interviews with mental health professionals and CESS members and triangulated them with four non-participant observations of ethical case consultations in psychiatry. Data were analyzed according to principles of grounded theory and are discussed from a normative perspective. Results: The analysis of the empirical data reveals a typology of three different ethical problems professionals want to refer to CESS: (1) Dyadic problems based on the relationship between patients and professionals, (2) triangular problems, where a third party is involved and affected as a side effect, and (3) problems on a systemic level. However, CESS members focus largely on types (1) and (2), while the third remains unrecognized or members do not feel responsible for these problems. Furthermore, they reflect a strong inner tension connected to their role as ethical experts which can be depicted as a dilemma. On the one hand, as ethically trained people, they reject the idea that their judgments have expert status. On the other hand, they feel that mental health professionals reach out for them to obtain guidance and that it is their responsibility to offer it. Conclusion: CESS members and professionals in mental healthcare have different ideas of the scope of responsibility of CESS. This contains the risk of misunderstandings and misconceptions and may affect the quality of consultations. It is necessary to adapt concepts of problem solving to practitioners' needs to overcome these problems. Secondly, CESS members struggle with their role as ethical experts. CESS members in psychiatry need to develop a stable professional identity. Theoretical clarification and practical training are needed.